Entre sacrificios y esperanzas: análisis de conflictos socioambientales en Bogotá desde una perspectiva de ecología política - Mariluz Nova Laverde; Milton Piñeros Fuentes; Jaime Edison Rojas Mora (Revista de Estudios Sociales)
This article examines socio-environmental conflicts through the lens of political ecology, focusing on the disconnection within the society-nature dialectic and the dualistic, hierarchical understanding of urban-rural dynamics. The study is set in Bogotá, specifically in the Pasquillita village, a territory affected by the Doña Juana landfill and urban expansion. Two research strategies are used: first, an analysis of the historical and material injustices shaping these territories, using a socio-environmental justice index to highlight the inequalities that form sacrifice geographies; and second, the documentation and systematization of local experiences, knowledge, and practices arising from processes of self-recognition and peasant resilience to identify the creation of geographies of hope. The socio-environmental justice index reveals significant disparities in the distribution of socio-economic and ecological conditions between rural and urban areas, while the documentation of experiences showcases innovative strategies of collective action by diverse communities with hybrid identities, who propose alternative ways of living and being rooted in the recovery of ancestral knowledge and peasant traditions. This is illustrated through work with the Asopasquillita peasant association, which is committed to healing and caring for the land. From this emerges the concept of wise territories as part of an ecology of knowledge, serving as a guiding principle for socio-environmental justice. This research contributes to critical geography, rural studies, and environmental justice by incorporating relational ontologies and a decolonial and ecofeminist perspective.